Inherited bone marrow failure with macrothrombocytopenia due to germline tubulin beta class I (TUBB) variant. (7th October 2022) - Shah, Yash B.; Lin, Ping; Chen, Stone; Zheng, Alan; Alcaraz, Wendy; Towne, Meghan C.; Gabriel, Courtney; Bhoj, Elizabeth J.; Lambert, Michele P.; Olson, Timothy S.; Frank, Dale M.; Ellis, Colin A.; et al.
Summary: Germline mutations in tubulin beta class I ( TUBB ), which encodes one of the β‐tubulin isoforms, were previously associated with neurological and cutaneous abnormalities. Here, we describe the first case of inherited bone marrow (BM) failure, including marked thrombocytopenia, morphological abnormalities, and cortical dysplasia, associated with a de novo p.D249V variant in TUBB . Mutant TUBB had abnormal cellular localisation in transfected cells. Following interferon/ribavirin therapy administered for transfusion‐acquired hepatitis C, severe pancytopenia and BM aplasia ensued, which was unresponsive to immunosuppression. Acquired chromosome arm 6p loss of heterozygosity was identified, leading to somatic loss of the mutant TUBB allele.